A comprehensive analysis of the intramural segment in interarterial anomalous coronary arteries using computed tomography angiography. Issue 4 (2nd May 2022) - Koppel, Claire J; Verheijen, Diederick B H; Kiès, Philippine; Egorova, Anastasia D; Lamb, Hildo J; Voskuil, Michiel; Jukema, J Wouter; Koolbergen, Dave R; Hazekamp, Mark G; Schalij, Martin J; Jongbloed, Monique R M; Vliegen, Hubert W
Abstract: Aims: An anomalous coronary artery originating from the opposite sinus of Valsalva (ACAOS) with an interarterial course can be assessed using computed tomography angiography (CTA) for the presence of high-risk characteristics associated with sudden cardiac death. These features include a slit-like ostium, acute angle take-off, proximal luminal narrowing, and an intramural segment. To date, no robust CTA criteria exist to determine the presence of an intramural segment. We aimed to deduct new CTA parameters to distinguish an intramural course of interarterial ACAOS. Methods and results: Twenty-five patients with an interarterial ACAOS (64% female, mean age 46 years, 88% right ACAOS) from two academic hospitals were evaluated. Inclusion criteria were the availability of a preoperative CTA scan (0.51 mm slice thickness) and peroperative confirmation of the intramural segment. Using multiplanar reconstruction of the CTA, the distance between the lumen of the aorta and the lumen of the ACAOS [defined as 'interluminal space' (ILS)] was assessed at 2 mm intervals along the intramural segment. Analysis showed a mean ILS of 0.69 ± 0.15 mm at 2 mm from the ostium. At the end of the intramural segment where the ACAOS becomes non-intramural, the mean ILS was significantly larger (1.27 ± 0.29 mm, P  < 0.001). Interobserver agreement evaluation showed good reproducibility (intraclass correlation coefficient 0.77, P  < 0.001). Receiver operator characteristic analysis demonstrated that at a cut-off ILS of <0.95 mm, an intramural segment can be diagnosed with 100% sensitivity and 84% specificity. Conclusion: The ILS is introduced as a novel and robust CTA parameter to identify an intramural course of interarterial ACAOS. An ILS of <0.95 mm is indicative of an intramural segment. Graphical Abstract: Graphical Abstract The ILS is introduced as a novel CTA parameter to identify an intramural course of interarterial ACAOS. An ILS of <0.95 mm is indicative of an intramural segment.